EI FORAS, MULIER, CZYLI ROZWÓD W KOMEDIACH PLAUTA - Tarwacka, Anna (Zeszyty Prawnicze, 2017)
El FORAS MULIER, VIZ. DIVORCE IN PLAUTUS’ COMEDIES Summary The Romans treated law as a very important element of everyday life. That is why their literature is so full of allusions to law. Plautus wrote his comedies for nearly 30 years, between 210 and 184B.C. His plays were based on the Greek Middle and New Comedy. It isnot always easy to distinguish the parts where he refers to Roman law fromthose where he simply translates the original text without making anychanges. In many of Plautus’ plays we can find information about divorce, though divorce was never shown on the stage for obvious moral reasons. In Menaechmi the husband threatens his wife with repudium because hefeels a slave in his own house - an ideal wife should - under no circumstances - spy on her husband or even ask him about his affairs. The position of a men in this relationship is rather weak - his wife brought a largedowry and he is simply afraid of what he could lose by ending his marriage. In Mercator Syra, a slave-woman, comments that husbans are allowed tohave sexual contacts with other women, whereas their wives can be easilyrepudiated even if seen outside their houses without a permission. Thereseems to have been no possibility for a woman to demand divorce in Romeof the III/II century B. C. Plautus uses this fact for comical purposes. InAmphitruo Alcumena speaks the formula of repudium as if backwords: tibihabeas res tuasy reddas meas, making it sound as if it was her husband to repudiate her. Plautus gives a lot of evidence that divorces were quite common in histimes and that the Romans knew perfectly all its legal aspects.